Endoscopic Treatment of Pilonidal Sinus Disease: State of Art and Review of the Literature - Manigrasso, Michele; Anoldo, Pietro; Cantore, Grazia; Chini, Alessia; D'Amore, Anna; Gennarelli, Nicola; Maione, Francesco; Marello, Alessandra; Schettino, Pietro; Sorrentino, Carmen; Vertaldi, Sara; Sosa Fernandez, Loredana Maria; et al. (Frontiers in Surgery, 2022)
Pilonidal sinus disease (PSD) is a chronic troublesome pathology of the natal cleft of the sacrococcygeal region, with an estimated incidence of 26 case out of 100,000 inhabitants. The aim of this review is to give a snapshot of the current literature on the endoscopic approach to the PSD. A search on endoscopic treatment of pilonidal disease was performed according to PRISMA guidelines, adopting the following search terms: (pilonidal OR sacrococcygeal) and (endoscopic OR VAAPS OR EPSiT OR minimally invasive OR video-assisted OR video assisted). 34 article were included in the final analysis, which of 23 on adults and 11 on pediatric population. The endoscopic approach is associated with painless postoperative pain, good aesthetic results, short time off-work and high patients’ satisfaction. Despite these advantages on short-term outcomes, results on recurrence rate in a long-term follow up are needed to definitively confirm the importance of this technique. the endoscopic approach is associated with significant postoperative advantages over other standard surgical approaches and it should be included in the surgical portfolio for the treatment of PSD. According to the Italian guidelines, this technique could be considered as the gold standard for limited pilonidal sinus disease. However, the favorable short-term-outcomes and the lack of reliable data on long-term follow up must be a stimulus to perform further high-quality studies to give definitive conclusions on this technique.